Please answer! Thank you
![Please answer Thank you class=](https://us-static.z-dn.net/files/d4c/328443405e407c76a2d8ea8642d68440.png)
Answer:
(x+30)/(5x+4)
Step-by-step explanation:
I got this by putting f(x) over g(x), which will give you (x^2+28x−60)/(5x^2−6x−8).
You can simplify this by factoring in both the numerator and denominator:
((x-2)(x+30))/((5x+4)(x-2))
You'll notice that both the numerator and denominator have (x-2) so you can cancel them out.
You'll get (x+30)/(5x+4).
Answer:
f(x) = (x+14)^2 -202
g(x) = 5(x -3/5)^2 -49/5
Step-by-step explanation:
Factor out 5 from the expression
g(x) =5(x^2 -6/5x) -8
To complete the square, the same value needs to be added to both sides
g(x) +? =5(x^2 -6/5x +?) - 8
To complete the square
x^2 -6/5+9/25=(x-3/5)^2 add 9/25 to the expression
g(x) + ? = 5 (X^2 -6/5x + 9/25) -8
Since 5(9/25) was added to the right-hand side, also add 5(9/25) to the left-hand side of the equation.
Simplify the answer
g(x)+9/5=5(x-3/5)^2 -8
Move the constant to the right-hand side and change its sign
g(x)=5(x-3/5)^2-8 -9/5
Calculate the diference for the final answer.